Lead Concentrations in Tissues of Pigeons (Columba livia) in the Urban Area of Comarca Lagunera, Mexico - Andrea Ocampo-Lopez; Cristo Omar Puente-Valenzuela; Homero Sánchez-Galván; Ana Alejandra Valenzuela-García; Josué Raymundo Estrada-Arellano; Ramón Alfredo Delgado-González; Jorge Alejandro Aguirre-Joya; Cristian Torres-León; Alejandra Ocampo-Lopez; David Ramiro Aguillón-Gutiérrez (Toxics)
The Comarca Lagunera is one of Mexico’s most important productive areas. Its main economic activities are livestock, agriculture, and the processing industry. A wide variety of industries emit wastes that are considered highly toxic environmental pollutants, which have strong negative impacts on public health. The objective of this work was to determine the lead concentrations present in tissues of pigeons (Columba livia) belonging to the urban area of the Comarca Lagunera, Mexico. Specimens were collected from the localities that comprise the region and the tissue extracted; the organs were dried, calcined, and diluted in an acidic HCl solution. Lead concentrations were obtained by atomic absorption spectrometry using the graphite furnace technique. The results demonstrate the presence of lead in all the tissues analyzed, with maximum concentrations of 191.14 mg/kg and minimum concentrations of 0.86 mg/kg, the area with the highest average concentration being Torreón, Coahuila (p = 0.030). The organ with the highest concentration was the bone (p = 0.000). Evidence of lead poisoning is presented in Columba livia tissues in the Comarca Lagunera, thus demonstrating the presence of this contaminant and the ability of these pigeons to function as bioindicators of environmental contamination.